Validity of Concentrated Sputum Microscopy versus Rapid Gene Xpert MTB/RIF in Case Detection of Presumptive Pulmonary Tuberculosis - Mahmood, Abdulkareem A; Al-Adly, Bassim Abullol; Kadhum, Qussay Mohsen (Hammurabi Journal of Medical Sciences, 2024)
Background: The diagnosis of pulmonary tuberculosis in Iraq started with direct sputum microscopy. The case detection rate is still below target level. Advance WHO-approved rapid diagnostic tests (Gen Xpert MTB/RIF) is now available for diagnosis. Objectives: To verify the validity and predictive value of direct and concentrated sputum microscopy in relation to Gen Xpert test for newly presumptive patients. Materials and Methods: A cross sectional study of 1175 patients attended the Respiratory and Chest Consultation Clinic in Najaf governorate, middle of Iraq. All patients suspected of having pulmonary TB submitted at least two early morning sputum specimens to detect acid fast Mycobacterium bacilli. One sputum sample from each patient was sent for Gen Xpert testing for both positive and negative result of smear microscopy. Direct and concentrated sputum smear with Ziehl Neelsen staining were prepared on the same specimen. The data was analyzed to estimate the accuracy rate, sensitivity and specificity, in addition to predictive value for positive and negative test. Results: From 1175 patients, only 396 completed their sputum submission for both sputum microscopy and molecular Gen Xpert per time. The sensitivity of direct smear microscopy versus concentrated sputum was 65% and 69.1% respectively with no significant difference. The specificity of direct smear result was 80.1% versus 76.1% for concentrated sputum smear. Conclusion: Sensitivity of both direct and concentrated sputum microscopy showed insignificant low detection rate. The direct smear test was found lightly more specific than concentrated smear.